Effect of perioperative statin therapy on renal outcome in patients undergoing cardiac surgery: A meta-analysis of randomized controlled trials. Issue 19 (May 2017) - Wang, Siyang; Yao, Huan; Yu, Hong; Chen, Chan; Zhou, Ronghua; Wang, Rurong; Yu, Hai; Liu, Bin
Abstract: Background: Acute renal injury (AKI) is a common renal complication after cardiac surgery. The aim of this study was to determine the effect of perioperative statin therapy (PST) on postoperative renal outcome in patients undergoing cardiac procedures. Methods: We searched for the reports that evaluating the effect of PST on renal outcomes after cardiac surgery between March 1983 and June 2016 in the electronic database Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE/PubMed, and EMBASE/OVID. Results: Nine randomized controlled trials (RCTs) enrolling 2832 patients, with 1419 in the PST group and 1413 in the control group, were included in this meta-analysis. Our results suggested that PST increased the incidence of postoperative renal complication (relative risk [RR] 1.18, 95% confidence interval [CI] 1.01–1.36, P  = .03) with low heterogeneity ( I 2  = 30%, P  = .18). Six studies with 3116 patients detected no significant difference in severe renal complication between PST and control groups (RR 1.23, 95%CI 0.84–1.79, P  = .28). Postoperative serum creatinine (sCr) at 48 hours was shown to be higher in the PST group (mean difference [MD] 0.03, 95% CI 0.03–0.03; P  < .01). The length of hospital stay was decreased slightly by 0.59 day in the PST group (95% CI –0.85 to –0.33; P  < .01). Conclusions: Perioperative statin therapy seems to jeopardize short-term renal outcome in patients undergoing cardiac surgery, but the occurrence of severe renal complication was not affected. Abstract : Supplemental Digital Content is available in the text